THE IMPACT OF INDUSTRIALIZATION, URBANIZATION, AND DROUGHT ON HEAVY METAL CONTAMINATION IN RIVER SYSTEMS IN KWAZULU-NATAL, SOUTH AFRICA: A CROSS-SECTIONAL STUDY. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Abstract Freshwater resources are vital for indigenous communities in Southern Africa, supporting livelihoods, agriculture, and biodiversity. However, increasing industrialization, urbanization, and agricultural runoff have led to severe contamination of river systems. While pollutants such as heavy metals are well-documented, the role of drought in intensifying their concentrations remains underexplored. This study investigates the relationship between low water levels and heavy metal pollution in rivers in KwaZulu-Natal, South Africa, focusing on how drought affects water quality. Methods A cross-sectional quantitative approach was used to analyze water quality under different seasonal conditions. Water samples were collected during high and low water periods to measure concentrations of lead (Pb), mercury (Hg), cadmium (Cd), and arsenic (As) using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Hydrological and meteorological data were also examined. Statistical analyses, including correlation and regression models, were applied to assess the influence of drought and pollution sources. Results Heavy metal concentrations increased significantly during drought conditions, with lead and cadmium exceeding WHO and South African water quality standards. Contamination was highest downstream of industrial and agricultural zones, where mercury and arsenic were alarmingly elevated. Additionally, ecological degradation was evident, including native vegetation loss and the spread of invasive species in polluted areas. Conclusion Drought amplifies the effects of chemical pollution in river systems, worsening ecological degradation and posing health risks to dependent communities. If left unchecked, ongoing urban and industrial growth will further compromise water quality and ecosystem health. Recommendation To address this issue, stricter enforcement of industrial discharge regulations is required. Regulatory frameworks must be strengthened to ensure industry compliance, supported by regular monitoring and stricter penalties for polluters. Proactive water management strategies are also needed to protect vulnerable communities and ecosystems from the combined threats of drought and pollution.